Software development in a web-based environment - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The advances of computer networks and data communications have led us to an era of network-based software. A very popular approach in developing such software is building the software on top of Web technologies. The capabilities of working under heterogenous platforms and seamless integration of static and dynamic information make Web application programs very different to those of ordinary, non-Web applications. Consequently, developing such a software needs a different approach. A research has been conducted to investigate the differences in their development issues. The research was performed by comparing the development methods of an application aimed to run in the two different environments. This paper reports the results and suggests some points on migrating an ordinary software to a Web-based environment. Understanding this is useful as the global computing tendency is shifting to distributed computing where differences and details in underlying hardware and operating systems are abstracted out of the users.